2007
DOI: 10.1128/aac.01216-06
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Inhibition of Plasmodium falciparum Rosette Formation by Curdlan Sulfate

Abstract: Spontaneous binding of infected erythrocytes to uninfected erythrocytes to form rosettes is a property of some strains of Plasmodium falciparum that is linked to severe complications of malaria. Curdlan sulfate (CRDS) is a sulfated glycoconjugate compound that is chemically similar to known rosette-inhibiting drugs such as heparin. CRDS has previously been shown to have antimalarial activity in vitro and is safe for clinical use. Here we show that CRDS at therapeutic levels (10 to 100 g/ml) significantly reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 18 publications
2
32
0
Order By: Relevance
“…Recently, a pivotal role for cytoadherence through the endothelial protein C receptor in the development of severe malaria was described (30). Cytoadhesion of Pf-iEs is mediated by members of the P. falciparum membrane protein 1 (PfEMP-1) family, which mediates parasite interactions with various host receptors, including CD36 (31), intercellular adhesion molecule 1 (ICAM-1) (32), and chondroitin sulfate A (CSA) (33,34), a receptor frequently associated with MiP (15,33,35) Glycosaminoglycans (GAGs), including heparin, have been employed as a strategy to prevent malaria complications due to their abilities to inhibit parasite cytoadhesion, to block invasion, and to disrupt rosettes (36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). However, the side effects of heparin, mostly serious bleeding (47), and the potential risk of contamination (because some GAGs are obtained from mammals) have hampered GAG-based adjunct therapies.…”
mentioning
confidence: 99%
“…Recently, a pivotal role for cytoadherence through the endothelial protein C receptor in the development of severe malaria was described (30). Cytoadhesion of Pf-iEs is mediated by members of the P. falciparum membrane protein 1 (PfEMP-1) family, which mediates parasite interactions with various host receptors, including CD36 (31), intercellular adhesion molecule 1 (ICAM-1) (32), and chondroitin sulfate A (CSA) (33,34), a receptor frequently associated with MiP (15,33,35) Glycosaminoglycans (GAGs), including heparin, have been employed as a strategy to prevent malaria complications due to their abilities to inhibit parasite cytoadhesion, to block invasion, and to disrupt rosettes (36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). However, the side effects of heparin, mostly serious bleeding (47), and the potential risk of contamination (because some GAGs are obtained from mammals) have hampered GAG-based adjunct therapies.…”
mentioning
confidence: 99%
“…This finding is not surprising but in concordance with the results of previous studies where it has been shown that some isolates are insensitive to heparin, heparin derivatives, and other rosette-disrupting sulfated glycoconjugates, even at very high concentrations. 23,24,44 In the present study, there was a statistically significant difference ( P < 0.05) between the complicated and mild groups, with a higher parasitemia and more isolates forming rosettes in the complicated malaria cases than in the mild malaria cases. Another observation is that the isolates that showed a rosetting phenotype in the mild group were of higher parasitemia and lower hemoglobin levels compared with the isolates in the same group that did not show any rosetting.…”
Section: Discussionmentioning
confidence: 71%
“…44,46 This compound has been reported to be effective in vitro at the concentration 50 μg/mL in the majority of 18 P. falciparum isolates from Kenyan children. The mechanism of rosette disruption The mean relative rosetting rate (the proportion of remaining rosettes after treatment compared with the control-treated erythrocytes) ± SEM is shown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies have identified sulphated glycoconjugate compounds such as heparin, fucoidan and curdlan sulphate as being effective at disrupting rosettes [13], [14], [15], [16]. Some of these sulphated polysaccharides not only disrupt rosetting, but also inhibit adhesion of IEs to host endothelial and placental receptors such as CSA and CD36 [17], [18], [19], [20].…”
Section: Introductionmentioning
confidence: 99%